2021
DOI: 10.14218/jcth.2021.00089
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Diagnostic Criteria of MAFLD and NAFLD in the Chinese Population: A Population-based Prospective Cohort Study

Abstract: Background and Aims Metabolic dysfunction-associated fatty liver disease (MAFLD) is a new concept, proposed in 2020; however, its applicability in Asia populations has yet to be evaluated. Therefore, we aimed to compare the difference in epidemiological and clinical characteristics between MAFLD and non-alcoholic fatty liver disease (NAFLD) among Asian populations. Methods Based on the Jinchang cohort, 30,633 participants were collected. The prevalence and incidence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 34 publications
3
35
0
1
Order By: Relevance
“…In conclusion, in line with the results reported by Yu et al ., 1 our data show that patients with MAFLD but not NAFLD only experienced significant impairment in HRQOL and performance of physical activities than healthy controls. This study adds to the growing body of evidence demonstrating the utility of the novel MAFLD definition 4 , 5 to identify patients at high risk of hepatic fibrosis, cardiovascular disease, chronic kidney disease, colonic polyps, and mortality 6 9 and the importance of consideration of MAFLD criteria in the clinical management of fatty liver disease.…”
mentioning
confidence: 49%
See 1 more Smart Citation
“…In conclusion, in line with the results reported by Yu et al ., 1 our data show that patients with MAFLD but not NAFLD only experienced significant impairment in HRQOL and performance of physical activities than healthy controls. This study adds to the growing body of evidence demonstrating the utility of the novel MAFLD definition 4 , 5 to identify patients at high risk of hepatic fibrosis, cardiovascular disease, chronic kidney disease, colonic polyps, and mortality 6 9 and the importance of consideration of MAFLD criteria in the clinical management of fatty liver disease.…”
mentioning
confidence: 49%
“…We read with great interest the article by Yu et al . 1 who reported that the metabolic dysfunction-associated fatty liver disease (MAFLD) criteria are more practical and improve the identification of high-risk patients with fatty liver disease compared with the previous nonalcoholic fatty liver disease (NAFLD) criteria. NAFLD and steatohepatitis are associated with significant impairment of health-related quality of life (HRQOL), 2 and as fibrosis progresses, the negative impact on HRQOL becomes more pronounced.…”
mentioning
confidence: 99%
“…Seven cohort studies among the general population reported data on ALT and AST levels for MAFLD and NAFLD. [5][6][7][8][9]15,18 Despite the considerable overlap between NAFLD and MAFLD (±80%), we observed slightly higher levels of ALT (mean difference 1.1 U/L; 95% CI 0.6-1.6) and AST (mean difference 0.8 U/L; 95% CI 0.4-1.2) among those with MAFLD compared to NAFLD (Figure S4). These differences became more evident in the non-overlapping groups of MAFLD-only and NAFLD-only.…”
Section: Mafld Is Associated With Higher Alt and Ast Levels Compared ...mentioning
confidence: 76%
“…Among those with FLD, 79.9% (95% CI 75.3-83.9) met both NAFLD and MAFLD definitions (overlap-FLD), 4.0% (95% CI 2.4-6.4) did not meet the novel MAFLD criteria but had NAFLD (NAFLD-only) and 15.1% (95% CI 11.5-19.5; Figure 3) was additionally captured by the novel MAFLD definition (MAFLD-only). [6][7][8][9][10]12,14,15,17,18 Among the non-general population, 11,13,16,19 MAFLD-only seems to be even more frequent (27.4%, 95% CI 13.0-48.9), while the prevalence of NAFLD-only remains low (5.0%, 95% CI 1.7-13.7; Figure S2).…”
Section: Mafld-only Is More Prevalent Than Nafldonlymentioning
confidence: 99%
“…The patients with MAFLD tended to have more severe metabolic derangements at baseline and poorer clinical outcomes such as incident general obesity, central obesity, DM and cerebrovascular events compared to patients with NAFLD in several retrospective studies 36 38 . Therefore, we tried to analyze the subjects according to change pattern of MAFLD additionally.…”
Section: Discussionmentioning
confidence: 99%